Biological properties of TW01 cells expressing latent membrane protein-1 gene of EBV-derived from nasopharyngeal carcinoma cells at different stages of malignancy - Tan, E.L.; Sam, C.K. (Experimental Oncology, 2007)
Background and Aim: Epstein—Barr virus (EBV), a human gammaherpesvirus is intimately associated with nasopharyngeal carcinoma (NPC), with the incidence of the virus detected in malignant tissues being close to 100% in NPC endemic areas. The viral latent gene, latent membrane protein 1 (LMP1), has all the typical characteristics of an oncogene and extensive studies have shown beyond doubt its abilities in cellular transformation giving rise to malignant phenotypes. The present study compares the gene sequence and biological properties of LMP1 gene derived from two patients with different stages of NPC – one presented with dysplastic, pre-malignant lesion and the other with malignant lesion. Methods: The sequences of the LMP1 genes derived from pre-malignant (NORLMP1) and malignant (NPCLMP1) tissues were compared. NORLMP1 and NPCLMP1 were expressed in TW01 cells and their biological properties conferred were assessed in terms of in vitro invasion capability, ability to resist apoptosis and regulation of E-cadherin (CDH1) expression. Results: NORLMP1 and NPCLMP1, possessed numerous amino acid changes with respect to the wild-type B95.8 LMP1. Both LMP1 variants demonstrated distinct biological properties when expressed in TW01 cells. NORLMP1-expressing TW01 cells exhibited more aggressive phenotypes than the NPCLMP1-expressing counterpart in terms of invasive ability, resistance to stimuli-induces apoptosis and regulation of CDH1 expression. Conclusion: It could be inferred from the present study that LMP1 genes derived from two patients with different stages of NPC differed in their gene sequences that manifested in distinct biological properties.